Istiratijiyyat Ta’liimu Al-Lughah Al-‘Arabiyyah Litarqiyah Itqaan Al-Mufradat - Az-Zahra, Maysa; Taufiq, Muhammad (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Mufradat or vocabulary is one of the language elements that must be given to Arabic language learners and is the basis for language learning. To improve the mastery of mufradat, a strategy is needed in its learning. Improving vocabulary is generally considered an important part of learning a language or developing one's skills in a language one already knows. Vocabulary learning should always be improved because there are difficulties for students in remembering and using the vocabulary that have been learned. The purpose of this study is to find out the strategies applied by Arabic language teachers in improving mastery of vocabulary and to find out whether the strategies applied are effective or not. Researchers used qualitative research methods, with data collection techniques through interviews aimed at teachers and students, observation and documentation. The result of this study is that Arabic teachers are ineffective in applying the right strategy to students to improve mastery of vocabulary. The strategy needed to improve the mastery of vocabulary is a simple repetition strategy, by the way every learning will begin, the teacher repeats the past learning and often looks for the meaning of the vocabulary to be learned